Berber Kramer, "Building Resilience through Financial Inclusion: A Review of Existing Evidence and Knowledge Gaps" - Kramer, Berber (2019)
Berber Kramer POLICY SEMINAR Building Resilience through Financial Inclusion: A Review of Existing Evidence and Knowledge Gaps Co-Organized by IFPRI and Innovations for Poverty Action (IPA) MAY 9, 2019 - 12:15 PM TO 01:45 PM EDT